사백산 물 추출물과 30% EtOH 추출물의 항염증 효과 비교연구 - 이동성(Dong-Sung Lee); 최현규(Hyun-Gyu Choi); 김경수(Kyoung-Su Kim); 김동철(Dong-Cheol Kim); 민홍기(Hong-Ki Min); 리빈(Bin Li); 김종수(Jong-Su Kim); 박준형(Jun-Hyeong Park); 오현철(Hyuncheol Oh); 김윤철(Youn-Chul Kim) (Yaghag-hoi-ji, 2012)
Sabaek-san has been used for the treatment of inflammatory diseases derived from the cold with high fever, cough, and lung dysfunction in Korea and China. There is no study for the comparison between different solvent extracts of Sabaek-san. We made two samples, one is Sabaek-san water extract (SBSW) and the other is Sabaek-san 30% EtOH extract (SBSE). Both extracts inhibited inducible nitric oxide synthase(iNOS) protein, reduced iNOS-derived nitric oxide (NO) production in lipopolysaccharide (LPS)-stimulated RAW264.7 cells. Also, they reduced tumor necrosis factor-${α}$ (TNF-${α}$) and interleukin-$1β$ (IL-$1β$) production. These anti-inflammatory effects caused by induction of heme oxygenase (HO)-1. HO-1 enzyme plays an important role of cellular anti-oxidant and anti-inflammatory systems. The induction of HO-1 is primarily regulated at the transcriptional level, and its induction by various inducers is related to the nuclear transcription factor-E2-related factor 2 (Nrf2). However, it is worth taking note that SBSE has more powerful anti-inflammatory effects than SBSW. In this study we suggest that different solvent extraction makes different therapeutic actions.